Історія Греції та Риму : методичні рекомендації - Шульга, С.А.; Shulga, S.A. (Волинський державний університет імені Лесі Українки, 2002)
Методичні рекомендації з курсу „Історія Стародавньої Греції та Риму” підготовлені для організації самостійної роботи студентів з вказаної навчальної дисципліни. Особлива увага звертається на вивчення та аналіз історичних джерел, що дає можливість засвоїти найважливіші проблеми курсу.The Methodological guide the course “History of the Ancient Greece and Rome” has been prepared to help the students to organize their independent work while learning the course of Ancient History. In the focus of attention is the analysis of the historscal sources which provides students with solid background for solving the most important problems in the course.
History of Greece and Rome : мethodological guide
Keywords: історія Греції та Риму; самостійна робота; методичні рекомендації; History of Greece and Rome; independent work; Methodological guide